Examining the Impact of Student Self-Efficacy on Motivation for Academic Achievement in Islamic Religious Education Subject - Anisah, Nurul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
At SMP Negeri 1 Bojong, significant academic and non-academic accomplishments have been consistently attained and maintained, cultivating students' self-efficacy and inspiring them to strive for excellence, fostering healthy competition within the school environment. This study aims to achieve three primary objectives: (1) assess the level of self-efficacy, (2) evaluate the degree of motivation for achievement, and (3) investigate the impact of self-efficacy on achievement motivation. Employing a quantitative research approach and utilizing ex post facto research methods, the study results reveal the following: (1) Self-efficacy falls within the moderate category, as evidenced by an average score of 79.80556 within the range of 71.7 - 87.8, (2) Achievement motivation also resides in the moderate category, with an average score of 79.77778 within the range of 70.36 - 89.19, and (3) A significant influence of self-efficacy on achievement motivation is established, supported by the T-test results (Sig. 0.000 <0.05 and Tcount 7.563 > Ttable 2.032), leading to the rejection of the null hypothesis (Ho) in favor of the alternative hypothesis (Ha). This relationship is further confirmed by the F-test (Sig. 0.000 <0.05 and Fcount 57.206 > Ftable 4.12), again rejecting Ho in favor of Ha. The simple linear regression test results, with an Fcount value of 57.206 and a significance level of 0.000 <0.05, demonstrate a correlation (R) value of 0.792 and a coefficient of determination (R Square) of 0.627. These findings indicate that the independent variable (self-efficacy) exerts a significant 62.7% influence on the dependent variable (achievement motivation).